Representation of Social Values in the Structure of the Markobar Tradition Language in Mandailing Wedding Customs - Nasution, Tanty Aidullia; Br. Perangin-angin, Alemina (Indonesian literature Program, Faculty of Humanities, Diponegoro University, 2025)
This study investigates the representation of social values embedded within the Markobar tradition language used in Mandailing wedding customs. Markobar, a linguistic and cultural expression, plays a significant role in the social interactions and ceremonial discourse of Mandailing weddings. The research adopts a semiotics approach by Rholand Barthes, analyzing the structural and symbolic elements of the language to identify and interpret the underlying social values. Key findings reveal that the language reflects principles such as mutual respect, kinship solidarity, and communal harmony, emphasizing the pivotal role of language as a medium for sustaining cultural identity. The study contributes to a deeper understanding of how linguistic practices preserve and propagate social values in traditional cultural settings.